RATIONALE AND SELECTION OF SOCIO-ECONOMIC PRIORITIES FOR DEVELOPMENT OF THE REGION - Тяжкороб , Ірина (Socio-economic relations in the digital society, 2019)
Іn conditions of increasing the autonomy of the regions, the effectiveness of the work of regional executive authorities depends, among other things, on the availability of scientifi c approaches to the defi nition of sectoral and territorial priorities. The article proposes a scheme for the adoption and implementation of management decisions in the rationale and selection of socio-economic, including investment, priorities for the development of the region. The essence of this process is characterized by numerous legal, organizational, information, resource and sociopsychological components. The components are determined by the conditions for the decision making and the nature of the problems to be solved for the development of the regional economy.